OP0120 A Systematic Analysis of the Safety of Prescribing Anti-Rheumatic Immunosuppressive and Biologic Drugs in Pregnant Women with Inflammatory Arthritis. (10th June 2014) - Panchal, S.; Flint, J.; van de Venne, M.; Piper, M.; Hurrell, A.; Cunningham, J.; Gayed, M.; Schreiber, K.; Anthanari, S.; Nisar, M.; Williams, D.; Khamashta, M.; et al.
Abstract : Background: The use of anti-rheumatic drugs in pregnancy is often complicated by concerns over their potential for adverse effects. Given that rheumatic diseases often affect women of childbearing age and may flare during pregnancy, the safety of anti-rheumatic drugs and immunosuppressant's are of particular importance. Practice has relied on information based mainly on experimental and animal studies. Previous systematic reviews have identified risks with various anti-rheumatic drugs and biologics. This systematic review is an update of consensus papers on anti-rheumatic drugs, biological agents and reproduction published in 2006/8. Objectives: This systematic review is an update of consensus papers on anti-rheumatic drugs, biological agents and reproduction published in 2006/8. Methods: A systematic search of PubMed and Embase was carried out using relevant keywords for pregnancy, lactation, rheumatoid arthritis (RA), psoriatic arthritis (PsA), inflammatory arthritis (IA), juvenile idiopathic arthritis (JIA) from 2006 onwards and drugs commonly prescribed in patients with rheumatic disease from 1966 onwards. Review articles and non-English language papers were excluded. Results: The search identified 43 papers published since the 2006/8 consensus papers describing relevant drug use in pregnant women with RA, PsA, IA and JIA. These consisted of 15 case reports, 7 case series, 16 cohort studies and 5 case-control studies. 4145 pregnancies were reported with an inflammatory arthritis. Over 4530 drug exposures were identified which includes steroids (346) DMARDs (AZA 210, HCQ 189, LFL 80, SSZ 57, MTX 15, MMF 1) and biologic therapies (278). Table 1 . illustrates the outcomes in pregnancy with some of the common drugs used in inflammatory arthritis. Conclusions: Evidence supports the safety of HCQ, AZA, SSZ and steroids in pregnancy. Data from a limited number of pregnancies exposed to anti-TNF alpha drugs predominantly in or immediately prior to the first trimester exposures indicates that the number of spontaneous miscarriages and congenital malformations do not appear to be increased. Further registry data is required for biologic drugs, before the safe use of these drugs can be advocated throughout pregnancy in patients with inflammatory arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5548